Facing climate change : low carbon urban waterfront at Puteri Harbour, Johor - Mohd Lazim, Nuramira (2018)
Low carbon landscape can be defined as an incorporation of landscape design in responding to climate change. This global issue needs to be readdressed to overcome this challenge. The effect of our ignorance actions towards environment has resulted us in facing the impact of it. Global warming, flood, urban heat island, an increasing of sea level and many other environmental issues are caused by human activities. Many forests are being developed into hard surface and structure with no intention to replace them back. An urban waterfront is seen as a potential in mitigating some of the effects such as urban heat island due to its geographical location. Puteri Harbour as a developing urban waterfront area needs to take a careful measure in controlling urbanisation. The aim for this study is to design a sustainable waterfront through low carbon landscape. The goal of this study is to produce a design to reduce and control climate change effect and creating a tourist allurement. Other than that it is also to design a sustainable waterfront that is harmonious with its natural ecosystem. The methodology that was used in this project consists of several stages. These stages are inventory and analysis, site synthesis and design strategies to solve the issues. The approach that was used is low carbon landscape by Chon, Choi, You, Lee, Seok (2014) which act as a guideline throughout the study. The overall result will be shown on the landscape master plan. With several methods being proposed, Puteri Harbour will be able to reduce carbon emitted even with urban activities. It is also will become a tourist spot and enhancing community bonding in the area.